Cytokine Profiling in Aqueous Humor Samples From Patients With Non-Infectious Uveitis Associated With Systemic Inflammatory Diseases - Bonacini, Martina; Soriano, Alessandra; Cimino, Luca; De Simone, Luca; Bolletta, Elena; Gozzi, Fabrizio; Muratore, Francesco; Nicastro, Maria; Belloni, Lucia; Zerbini, Alessandro; Fontana, Luigi; Salvarani, Carlo; et al. (Frontiers in Immunology, 2020)
Non-infectious uveitis are intraocular inflammatory conditions caused by dysregulated activation of the immune response without any detectable infectious agents. The aim of this study was to explore potential markers and therapeutic targets for two distinct types of non-infectious uveitis associated with Behçet's disease (BD) and Vogt Koyanagi Harada (VKH) disease. Concentrations of 27 cytokines were investigated in aqueous humor (AH) samples from patients with active uveitis vs. healthy controls (HC) (n = 10 patients with BD-associated uveitis; n = 10 patients with VKH-associated uveitis; n = 10 HC) using the Bio-Plex ProTM human cytokine group I panel. Additionally, leukocytes in AH samples were counted with hemocytometers and characterized by flow cytometry. Eleven cytokines were differentially expressed between patients with uveitis and HC with a median concentration greater than 10 pg/ml. IL-6, IP-10, G-CSF, and IFNγ showed higher concentrations in AH samples from both BD and VKH patients while IL-2, IL-8, IL-13, TNFα, eotaxin, IL-1ra showed statistically significant higher concentrations only in AH samples from BD patients. GM-CSF was the sole cytokine with an opposite profile showing decreased levels in AH samples from BD patients. IL-1ra and IL-6 were detected at higher frequencies in AH samples from BD and VKH patients compared with those from HC while IFNγ and TNFα were not detected in HC. The concentrations of IL-6, IL-8, IP-10, G-CSF, IFNγ, TNFα, eotaxin, IL-1ra positively correlated with the concentrations of leukocytes in AH, suggesting that such cytokines can be produced by immune cells and/or attract and/or promote proliferation and survival of immune cells in these types of uveitis. The correlation matrix of cytokine concentrations in AH samples revealed that IFNγ, TNFα, eotaxin, IL-6, G-CSF highly correlated each other. The ratios of cytokine concentrations between AH and plasma intra-individuals showed that IL-2, IL-6, IP-10, GM-CSF were increased intraocularly. In conclusion, AH sampling followed by multiplex analysis of cytokines should be fostered in non-infectious uveitis to identify cytokines dysregulated intraocularly in each individual laying the groundwork for precision medicine.